Haskell in depth - Bragilevsky, Vitaly (Manning Publications, 2021)
Haskell in Depth unlocks a new level of skill with this challenging language. Going beyond the basics of syntax and structure, this book opens up critical topics like advanced types, concurrency, and data processing. You'll discover key parts of the Haskell ecosystem and master core design patterns that will transform how you write software.
Online resource; title from title details screen (O'Reilly, viewed December 10, 2024)
Keywords: Haskell (Computer program language); Functional programming (Computer science); Haskell (Langage de programmation); Programmation fonctionnelle; Audiobooks; Livres audio